Usefulness of the Alvarado scale in pediatric patients with abdominal pain at the University Hospital of Valle del Cauca, Colombia - Villegas-Arenas, Dolly; Echandia-Villegas, Connie Alejandra; Echandía-Alvarez, Carlos Armando (Universidad y Salud, 2025)
Introduction: The diagnosis of appendicitis in young boys and preadolescent girls who are beginning their sexual development is difficult. Objective: To determine the usefulness of the Alvarado scale in children aged between 1 to 14 years, who have abdominal pain. Materials and methods: Cross-sectional study using information from clinical records of minors who were admitted due to abdominal pain at the University Hospital of Valle del Cauca, Colombia, between January 2017 and December 2018. A cut-off point greater than seven was applied to estimate both the operative characteristics of the scale and its operative characteristics curve. Results: 323 out of the 451 records analyzed included children with acute appendicitis. Male patients with an average age of 9.4 ± 2.8 years predominated, 26% of which experienced appendix rupture. 66.6% of the 13 minors aged 4 years old diagnosed with appendicitis also had appendix rupture. The scale had a 96% specificity and a 38.8% sensitivity. Likewise, a value of 7.5 was the best cut-off value of the ROC curve to discriminate between children with and without appendicitis. Conclusion: The scale was accurate to discriminate between children with and without appendicitis. Early ultrasonography is recommended for children under 4 years of age.